Effect of baru (Dipteryx alata Vog.) addition on the composition and nutritional quality of cookies - CAETANO,Kelly Aparecida (2017)
Abstract The use of the defatted baru almond (Dipteryx alata Vog.) prevents the production of waste residues after extraction of its oil (partially defatted baru flour), representing a process of interest from an environmental point of view. The aim of this study was to prepare oat cookies with functional properties, replacing 100% soy oil for baru oil and 30% wheat flour for partially defatted baru flour (baru cookie). Baru cookies presented a higher moisture (7.80%), probably due to the high content of dietary fiber (3.78%), resulting in a lower calorie content (457.46 kcal.100 g–1), compared to traditional oat cookies. Changing the formulation resulted in the enrichment of a number of microelements, including phosphorus (~ 197.90 mg.100 g–1) and iron (~ 21.56 mg.100 g–1). Baru oil increased the concentration of unsaturated fatty acids (~ 76.11%), consisting of approximately 50.37% monounsaturated (MUFA), and 25.74% polyunsaturated fatty acids (PUFA). The total phenolic compound content was approximately doubled in the baru cookie. As such, the baru cookie presents an interesting composition from a nutritional point of view, having a high protein and dietary fiber content, in addition to presenting substantial concentrations of iron and oleic acid, and may be used as part of a healthy diet.